(untitled) (Globalization and Business, 2023)
Local self-government, as one of the most basic forms of the constitutional order, can be credible only in case of its practical coexistence with the public authorities. Local self-government, as a special form of people power, guarantees non-interference of the State in addressing local affairs. The constitutional-legal model of local self-government in Georgia is based on the renewal of democratic traditions of self-organization of the population and territorial self-government. This is primarily due to organizational specificities of local self-government. In addition, the constitutional norms establish a high level of independence of local self-government in addressing local affairs. However, the influence of the State at the level of local democracy persists in any case. In the current context, local self-government is an integral part of a unified system of public relations, which is organizationally, institutionally and functionally closely linked to other levels of public administration. We believe that a task of local self-government, unlike the pubic authorities, is not to try to regulate everything, but to coordinate and harmonize the governance "from above" and self-regulation "from below". In public administration there is a need to align people’s and the self-government’s interests. Public governance is intended to take into account the existing reality, to objectively assess the role and place various norms and carry out governance activities only on that basis. Nearly thirty years of experience in public-political governance in Georgia have demonstrated that in post-socialist Georgia, clearly, there is a gradual redistribution of power from the legislature to the executive branch. In addition, the country is witnessing a transformation in public-political governance.